Impatience, anticipatory feelings and uncertainty: A dynamic experiment on time preferences - Marco Casari; Davide Dragone (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
We study time preferences in a real-effort experiment with a one-month horizon. We report that two thirds of choices suggest negative time preferences. Moreover, choice reversal over time is common even if temptation plays no role. We propose and measure three distinct concepts of choice reversal over time to study time consistency. This evidence calls for an important role for anticipatory feelings and uncertainty in intertemporal behavior.
Keywords: C91; D01; D80; D90; 330; negative time preferences; choice reversal; risk; time inconsistency; real-effort experiment; Zeitpräferenz; Risiko; Test